Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1001/archgenpsychiatry.2012.23
|View full text |Cite
|
Sign up to set email alerts
|

Probing Thalamic Integrity in Schizophrenia Using Concurrent Transcranial Magnetic Stimulation and Functional Magnetic Resonance Imaging

Abstract: Context Schizophrenia is a devastating illness with an indeterminate pathophysiology. Several lines of evidence implicate dysfunction in the thalamus, a key node in the distributed neural networks underlying perception, emotion, and cognition. Existing evidence of aberrant thalamic function is based on indirect measures of thalamic activity, but dysfunction has not yet been demonstrated with a causal method. Objective Test the hypothesis that direct physiological stimulation of cortex will produce an abnorma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 81 publications
2
43
1
Order By: Relevance
“…The thalamus is connected to all cortical areas and conveys information to the neocortex, including information from the basal ganglia. Though a number of other studies have identified thalamic connectivity changes in the chronic stage of schizophrenia, 17,19,[22][23][24] such studies provide little information about early illness pathophysiology. In contrast, studies of FE schizophrenia have the advantage to specify brain changes at illness onset, thus providing crucial information about the pathogenesis of schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The thalamus is connected to all cortical areas and conveys information to the neocortex, including information from the basal ganglia. Though a number of other studies have identified thalamic connectivity changes in the chronic stage of schizophrenia, 17,19,[22][23][24] such studies provide little information about early illness pathophysiology. In contrast, studies of FE schizophrenia have the advantage to specify brain changes at illness onset, thus providing crucial information about the pathogenesis of schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24] Despite numerous leads, the reported findings are somewhat inconsistent and the core regions associated with the pathogenesis of schizophrenia still remain controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Schizophrenia is in the recent literature increasingly being recognized as a disorder of internal brain dynamics [6][7][8][9][10]. Accordingly, in the following sections, thalamic abnormalities in schizophrenia will be reviewed followed by a discussion of how sleep brain rhythms are affected in this illness.…”
Section: Introductionmentioning
confidence: 99%
“…Namely, this illness is associated with thalamic abnormalities that affect the HO thalamic relays, which are tasked with relaying information between cortical areas. In an interesting study that combined functional neuroimaging and transcranial magnetic stimulation (TMS), Guller et al (2012) found that TMS stimulation of the precentral gyrus in individuals with schizophreArch Neurosci. 2017; 4(3):e57105.nia resulted in reduced thalamic activation, which was correlated with the severity of positive symptoms in those individuals (8).…”
mentioning
confidence: 99%
“…In an interesting study that combined functional neuroimaging and transcranial magnetic stimulation (TMS), Guller et al (2012) found that TMS stimulation of the precentral gyrus in individuals with schizophreArch Neurosci. 2017; 4(3):e57105.nia resulted in reduced thalamic activation, which was correlated with the severity of positive symptoms in those individuals (8). They also reported reduced secondary cortical activation, which was statistically related to the reduced thalamic activation.…”
mentioning
confidence: 99%